Decision analysis of pepper (Piper nisrum L.) farmers in choosing organic farming system. Issue 3 (July 2021) - Fudjaja, L; Viantika, N M; Heliawaty,; Tenriawaru, N; Aulia, I
Abstract: All Organic farming considered as one of the solutions to the green revolution. Organic farming business is relatively profitable because the selling price of organic commodities is more expensive than non-organic. On contrary farmers' interest were still lacking in organic farming. This study aims are to analyze the influences factors of pepper farmers in decision making on choosing organic farming systems, so as to analyze the ratio of income levels of organic pepper farmers compared to non-organic pepper growers. Descriptive analysis, logistic regression analysis and income comparison analysis was applied. The results showed that age, level of education and price were some factors that influenced the decision of pepper farmers on choose an organic farming system. Furthermore, organic pepper farmer incomes is higher than the income of non-organic pepper farmers by a difference at IDR 11, 884, 591.3.